Does a 'teen-birth' have longer-term impacts on the mother? suggestive evidence from the British Household Panel Study - John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2003)
The paper studies associations between a womans age at becoming a mother and subsequent outcomes, such as her living standard, when she is aged 30-51. The data come from the British Household Panel Survey over the years 1991-2001. The analysis suggests that having a teen-birth, particularly when aged under 18, constrains a womans opportunities in the marriage market in the sense that she finds it more difficult to find and retain a partner, and she partners with more unemployment-prone and lower earning men. Teenage mothers are much less likely to be a homeowner later in life, and her living standard, as measured by equivalent household income, is about 20% lower.
Keywords: 330